UJI KEPEKAAN BAKTERI METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS TERHADAP ANTIBIOTIK VANCOMYCIN DENGAN METODE MACROBROTH DILUTION - , PRIMADHY RAHARDIAN WIJAYA; , dr.Titik Nuryastuti,M.Si.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Methicillin-Resistant Staphylococcus aureus is one of main pathogen causing infection in human beings. Methicillin-Resistant Staphylococcus aureus infections is often severe and hard to treat because itâs capability to resists any beta lactams antibiotics and its fast ability to develop resistant against various antibiotics. Even, some of strains are found to be resistant against Vancomycin that has been a drug of choice to treat this bacterial infection. This researchâs objective is to know the sensitivity of MRSA to antibiotic vancomycin in Yogyakarta. Objectives : To know Vancomycin sensitivity against Methicillin Resistant Staphylococcus aureus with macrobroth dilution method. Method : This study used observational design. The materials were Vancomycin antibiotic and Methicillin-Resistant Staphylococcus aureus isolate collections of Laboratorium of Microbiology Faculty of Medicine Universitas Gadjah Mada. Minimal Inhibitory Concentration (MIC) and Minimal Bacteriocidal Concentration (MBC) of Vancomycin against Methicillin-Resistant Staphylococcus aureus were examined using Macrobroth Dilution and match it with CLSI standard. Results : Minimal Inhibitory Concentration (MIC) of 5 Methicillin-Resistant Staphylococcus aureus isolates tested against Vancomycin were 80% sensitive, 20% intermediate, and 0% resistant. Conclusion : Vancomycin has antibacterial effect and still sensitive againts Methicillin-Resistant Staphylococcus aureus